To Guard or Not to Guard? Territorial Behavior Among Foraging Societies (Undergraduate Research Journal; 2017, 2017)
Variation in territory size, population density, and residential mobility among small scale hunting and gathering societies tends to co-vary with territorial behaviors. Specifically, groups living in larger areas, at lower population densities with higher mobility are less likely to exhibit territorial behavior than their counterparts in smaller areas. Based on models from behavioral ecology, we suggest that this variation is due to underlying levels of environmental productivity: where productivity is high, resources are abundant, allowing for dense populations that do not need to move as much, which creates smaller territories that can be defended. Here we compile and evaluate a global data set of ethnographic and ethnohistoric hunter-gatherers linked to remotely sensed data on environmental productivity to test this hypothesis.
Keywords: Territoriality, Foraging, Subsistence, Behavioral Ecology, Hunting, Gathering